2012
DOI: 10.1002/pssb.201248301
|View full text |Cite
|
Sign up to set email alerts
|

Photostimulated detection of defect formation in BaF2 under irradiation of synchrotron radiation

Abstract: We have investigated the defect formation processes of BaF2 single crystals under vacuum ultraviolet radiation with the use of combination spectroscopy of synchrotron radiation (SR) and laser. The defect formation efficiency was measured as a function of excitation photon energy of SR by means of a laser‐induced luminescence method. It was found that the efficiency depends significantly on the excitation photon energy. We show that the dependence can be explained in terms of the diffusive motion of hot conduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 26 publications
(41 reference statements)
0
2
0
Order By: Relevance
“…It is clearly visible that the periodic nanostructures observed in the XUV-CDL irradiation experiment differ from the morphology of all the damage patterns observed on alkali-earth-halide surfaces exposed to radiation of various kinds in numerous studies reported earlier [26][27][28][29][30][31][32][33][34][35][36][37][38][39]. We should keep in mind that an attenuation length of 46.9-nm XUV-CDL radiation in BaF 2 is very short, i.e., only about 10 nm [40,41].…”
Section: Discussion and Outlookmentioning
confidence: 90%
See 1 more Smart Citation
“…It is clearly visible that the periodic nanostructures observed in the XUV-CDL irradiation experiment differ from the morphology of all the damage patterns observed on alkali-earth-halide surfaces exposed to radiation of various kinds in numerous studies reported earlier [26][27][28][29][30][31][32][33][34][35][36][37][38][39]. We should keep in mind that an attenuation length of 46.9-nm XUV-CDL radiation in BaF 2 is very short, i.e., only about 10 nm [40,41].…”
Section: Discussion and Outlookmentioning
confidence: 90%
“…A detailed characterization of ablated areas has not been performed. As to ionizing radiation, the defect formation was induced in BaF 2 and CaF 2 by synchrotron radiation [38] and 850-eV [39] electrons, respectively. The results are similar to those obtained with intense UV radiation.…”
Section: Discussion and Outlookmentioning
confidence: 99%